2009
DOI: 10.1007/s10549-009-0657-x
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 promotes breast carcinoma proliferation and invasion/metastasis in vitro and in vivo

Abstract: A yeast two-hybrid system was utilized to identify novel PI3K p110alpha-interacting proteins, of which receptor of activated protein kinase C1 (RACK1) was chosen for successive detailed analyses. Our aim was to investigate the function(s) of RACK1 and its involvement in mechanisms of breast carcinoma proliferation and invasion/metastasis. Experiments in breast carcinoma cell lines stably transfected with RACK1, as well as nude mouse models, showed that RACK1 promotes breast carcinoma proliferation and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
63
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 42 publications
10
63
2
Order By: Relevance
“…In 160 breast carcinoma cases, survival analyses established that RACK1 is an independent prognostic factor for poor outcome (Po0.001) (Cao et al, 2009(Cao et al, , 2010a. Our results are consistent with the findings of Wang et al in oral squamous cell carcinoma (Wang et al, 2008.…”
supporting
confidence: 92%
“…In 160 breast carcinoma cases, survival analyses established that RACK1 is an independent prognostic factor for poor outcome (Po0.001) (Cao et al, 2009(Cao et al, , 2010a. Our results are consistent with the findings of Wang et al in oral squamous cell carcinoma (Wang et al, 2008.…”
supporting
confidence: 92%
“…We have read with great interest the recent article by Cao X [1] in which the authors looked at the protein expression of RACK1 in human breast cancer and showed that high levels were predictive of a poor clinical outcome in vitro and in vivo. We have analyzed RACK1 mRNA expression RACK1 (primers:aaaaccatcaagctatggaa, RACK1F1actgaacctgaccgtacaacaggagacgatgataggg, RACK1Zr 1) in 127 human breast cancer and in 33 non-cancerous breast tissue specimens by using rt-PCR technology following RNA extraction from frozen samples.…”
Section: To Cite This Versionmentioning
confidence: 99%
“…
Dear editor, Our experiments in 160 breast carcinoma cases, survival analyses established that RACK1 is an independent prognostic factor for poor outcome (P < 0.001) [1].Furthermore, in breast carcinoma cell lines stably-transfected with RACK1, as well as nude mouse models, showed that RACK1 promotes breast carcinoma proliferation, migration and invasion/metastasis in vitro and in vivo [2, 3]. Our results are consistent with the finding of Wang et al in oral squamous cell carcinoma [4,5].

We strongly suggest that the authors should consider experiments in breast cancer cell lines to verify the findings in vivo.

Should you have any question please do not hesitate to contacting with me.

Preference:

…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Rack1 also promotes degradation of HIF1a (Liu et al, 2007) and BimEL (Zhang et al, 2008) by mediating the interaction between each of these proteins and the ubiquitin complex. Importantly, accumulating clinical data indicate that Rack1 is involved in cancer cell proliferation, invasion and metastasis, and is a novel biomarker for diagnosis and prognosis prediction (Wang et al, 2008;Nagashio et al, 2009;Cao et al, 2009aCao et al, , 2009b. These types of findings suggest that more studies are needed to increase our understanding as to how Rack1 functions in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%